2013
DOI: 10.1371/journal.pcbi.1003127
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-based Screening Strategy for Multitarget Inhibitors of Diverse Proteins in Metabolic Pathways

Abstract: Many virtual screening methods have been developed for identifying single-target inhibitors based on the strategy of “one–disease, one–target, one–drug”. The hit rates of these methods are often low because they cannot capture the features that play key roles in the biological functions of the target protein. Furthermore, single-target inhibitors are often susceptible to drug resistance and are ineffective for complex diseases such as cancers. Therefore, a new strategy is required for enriching the hit rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…After identifying these potential target proteins, we integrated molecular docking (GEMDOCK, Yang and Chen, ) and statistically analyzed thousands of docked poses for site‐moiety maps (SiMMaps, Chen et al ., ) to further investigate and evaluate their binding environments. Our previous studies have shown that GEMDOCK has a similar performance to other docking methods (Ewing et al ., ; Kramer et al ., ) and was successfully used to identify novel inhibitors and binding sites (Chin et al ., ; Hsu et al ., , ; Yang et al ., ). An anchor of a SiMMap possesses three properties: a binding subpocket with interacting residues, the moiety composition of screening compounds, and the pocket–moiety interaction type (electrostatic, hydrogen‐bonding, or vdW).…”
Section: Resultsmentioning
confidence: 99%
“…After identifying these potential target proteins, we integrated molecular docking (GEMDOCK, Yang and Chen, ) and statistically analyzed thousands of docked poses for site‐moiety maps (SiMMaps, Chen et al ., ) to further investigate and evaluate their binding environments. Our previous studies have shown that GEMDOCK has a similar performance to other docking methods (Ewing et al ., ; Kramer et al ., ) and was successfully used to identify novel inhibitors and binding sites (Chin et al ., ; Hsu et al ., , ; Yang et al ., ). An anchor of a SiMMap possesses three properties: a binding subpocket with interacting residues, the moiety composition of screening compounds, and the pocket–moiety interaction type (electrostatic, hydrogen‐bonding, or vdW).…”
Section: Resultsmentioning
confidence: 99%
“…2 While a number of studies have sought to identify inhibitors of other enzymes in the pathway, [3][4][5][6][7][8][9] a relatively small number of compounds have been identified that block the pathway's fourth reaction, the NADPH-dependent conversion of 3-dehydroshikimate to shikimate. [10][11][12] This reaction is catalyzed by shikimate dehydrogenase (AroE). 1 Here, we have designed an in vitro screen to evaluate the ability of compounds from a combined library of more than 5500 small molecules to inhibit the AroE enzyme from the bacterium, Pseudomonas putida (PpAroE).…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the use of PA/CPA models in drug discovery, we proposed an integrated anchor-based virtual screening method which employed pharmacophore anchors from the models in virtual screening to discover true inhibitor hits (Methods: Integrated anchor-based screening approach). Our previous studies showed the applicability of anchors to identify true hit compounds [ 33 , 34 ]. Here, we employed this strategy against DENV NS3 protease for screening of FDA drug dataset (Methods: Proteins-compound datasets).…”
Section: Resultsmentioning
confidence: 99%